Risk Analysis of the Fish Crackers Production Process Using FMEA and FTA Methods at CV. Tayamum K.A.M - Moh. Abi Mas Walid; Hidayat Hidayat; Yanuar Pandu Negoro (Universitas Islam Raden Rahmat, Malang, 2025)
CV. Tayamum K.A.M is a small micro business that manages crackers made from various sea fish. During the production process, the company often faces problems. This research was conducted to evaluate the performance of the production process using FMEA and FTA methods. The results of the FMEA calculation used to determine the severity level, occurrence level, detection level which later obtained the highest RPN value which is a cracked product that is not up to cuil with a total RPN of 697, FTA analysis shows the root causes of errors such as not re-checking, improper drying time and poor air circulation. After knowing the results of the root cause of the problem, an improvement proposal is given, namely rechecking the machine before use, paying attention to weather conditions when drying, and adding enough ventilation holes or blowers.